ASPECTOS PSICODINÂMICOS E CAPACIDADE MATERNA DE MÃES DE CRIANÇAS ABRIGADAS - Costa, Márcia Chicareli (2008)
This paper aimed at investigating aspects of the intrapsychic dynamics of mothers whose children live in shelters due to court order and identifying the protective resources used by these mothers. To meet these purposes, a clinical investigation studying three cases of sheltered children s mothers was done. Two instruments were used: a) Interview Script Theme scripts to be covered during one or more non-directive interviews of clinical scope, inorder to help investigate the psychodynamics of these mothers. b) Drawings and Storytelling Procedure Projective technique which associates the use of drawings to stories as a mean of exploring the contents of personality freely and dynamically. This technique allows the study of formal and structural characteristics of the personality, as it has the singularity of facilitating the expression of unconscious aspects related to present anguishes points, differing focus, and emerging disorders. These procedures were used inside the institution (shelter) in which the children lived. The main results common to the three cases were: Ambiguity and Development Impendings - the first interviewed mother attacks at the same time the mother that left her (the biological mother and the adoptive mother), in search of na idealized mother. This ambiguity impedes her development. The same attempt of idealisation was observed on the second interviewed mother. She shows embarassement in accepting her life and can´t realize that the approaching of her mother is because of an acquired disease and not for continence. The third and last interviewed mother shows persecutive contents when facing the sheltering of her children and embarassement to feel greatful. The prevailing mechanisms that appear on the three cases are: Idealization and regression to primitive stages. Depression, difficulty to elaborate the depressive position are also observed. These mothers can´t continuously experience the psychic reality that would imply on the elaboration of depressive position, since they can´t do it, though they attempt to compare between the internal and external worlds, this would lead them to a better understanding of the similarities and differences, so the parents figure (mainly the mother's) becomes divided between terrifying and idealised, but the prevailing mechanisms are their fantasies that provide idealisation; massive projective identification. The persecution and guilty seem to indicate at the same time the depression that can be so strong that leads to the enhancement of these feelings. There´s the presence of envy that also enhances the persecution anguishes, requiring defense mechanisms that violates the psychic functions.(AU)